Addressing special educational needs and disability in the curriculum maths - Wallace, Max (Mathematics teacher) (Routledge, 2018)
"The SEND Code of Practice (2015) reinforced the requirement that all teachers must meet the needs of all learners. This topical book provides practical, tried and tested strategies and resources that will support teachers in making maths lessons accessible and interesting for all pupils, including those with special needs. The author draws on a wealth of experience to share his understanding of special educational needs and disabilities and show how the maths teacher can reduce or remove any barriers to learning."--Provided by publisher.